Machine Learning : A Journey To Deep Learning with Exercises And Answers - Wichert, Andreas, author 636004; Sa-Couto, Luis, author 636005 (New Jersey : World Scientific)
"This unique compendium discusses some core ideas for the development and implementation of machine learning from three different perspectives - the statistical perspective, the artificial neural network perspective and the deep learning methodology.The useful reference text represents a solid foundation in machine learning and should prepare readers to apply and understand machine learning algorithms as well as to invent new machine learning methods. It tells a story outgoing from a perceptron to deep learning highlighted with concrete examples, including exercises and answers for the students."--